2016
DOI: 10.7717/peerj.2576
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IL-6 and IL-28B gene polymorphisms on treatment outcome of chronic hepatitis C infection among intravenous drug users in Croatia

Abstract: BackgroundSeveral genes and their single nucleotide polymorphisms (SNPs) are associated with either spontaneous resolution of hepatitis C infection or better treatment-induced viral clearance. We tested a cohort of intravenous drug users (IVDU) diagnosed with chronic hepatitis C virus (HCV) for treatment response and its association with the SNPs in the interleukin-6 (rs1800795-IL6) and the interleukin-28B (rs12979860-IL28B) genes.MethodsThe study included 110 Croatian IVDU positive for anti-HCV antibody. Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In contrast, a study showed that the GG genotype of the rs1800795 −174 G/C polymorphism is associated with high serum levels of IL-6 and the likelihood of sustained virologic response (SVR) in patients co-infected with HCV and HIV [48] . Similarly, other studies have demonstrated that the CC genotype of the rs1800795 −174 G/C polymorphism is associated with low production of IL-6 and an attenuated immune response against chronic HCV [49] , [50] . In contrast, it has also been reported that genetic polymorphisms of IL-6 in rs1800796 (-572 G > C) were not associated with HCV infection and development of hepatocellular carcinoma (HCC) in an Egyptian population [51] .…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, a study showed that the GG genotype of the rs1800795 −174 G/C polymorphism is associated with high serum levels of IL-6 and the likelihood of sustained virologic response (SVR) in patients co-infected with HCV and HIV [48] . Similarly, other studies have demonstrated that the CC genotype of the rs1800795 −174 G/C polymorphism is associated with low production of IL-6 and an attenuated immune response against chronic HCV [49] , [50] . In contrast, it has also been reported that genetic polymorphisms of IL-6 in rs1800796 (-572 G > C) were not associated with HCV infection and development of hepatocellular carcinoma (HCC) in an Egyptian population [51] .…”
Section: Discussionmentioning
confidence: 67%
“…Low‐producing or high‐producing IL‐6 polymorphisms were related clearance of viral infection, sustained virologic response, and attenuated adaptive immune response (Barrett et al, 2001; Bogdanović et al, 2016; Nattermann et al, 2007). A recent meta‐analysis showed that mean IL‐6 concentrations were dramatically increased in patients with cytokine release syndrome, sepsis, and acute respiratory distress syndrome unrelated to Covid‐19 (Leisman et al, 2020).…”
Section: Genetic Variations Of Immunity Componentsmentioning
confidence: 99%
“…IL6 was the most reported gene to be associated with HCV infected persons or HCC patients caused by chronic HCV infection. SNP rs1800795 was associated with treatment of HCV patients infected by drug injection in Croatian (Bogdanovic et al, ). Moreover, the polymorphisms of the IL6 gene were reported to influence the histologic progression and clinical outcomes of HCV patients (Falleti et al, ; Sghaier et al, ).…”
Section: Discussionmentioning
confidence: 99%